Käyttöliittymän rooli graafisten seikkailupelien peliympäristön havainnoinnissa - Koskela, Jukka (2025)
This master’s thesis examines how the user interface affects game world exploration in graphical adventure games. The research was conducted by comparing two of the most prolific user interface types used in the genre point and click, and first person view. Close gaming was chosen as the research method for the comparison, and it was supported by specifically created usability heuristics, based on existing video game heuristics. Close gaming was done with the game Sherlock Holmes: The Awakened (2008), a game that could be played with both user interface types. Research revealed that though point and click has it’s advantages, playing from first person view proved a more satisfying experience. Additional result of the research were the newly created heuristics for evaluating usability in graphical adventure games.